Humor w memach internetowych związanych z pandemią koronawirusa: analiza wybranych przykładów - Małgorzata Karczewska (In Gremium. Studies in History, Culture and Politics, 2022)
In 2020 the coronavirus pandemic dominated global life bringing fear and death. Apart from the health crisis, a significant economic and social turmoil appeared following restrictions implemented worldwide to prevent the spread of the virus. One of the ways to cope with this stressful situation is humour giving relief and offering a chance to see reality from a distance. Therefore, numerous internet memes were created to depict everyday life in the pandemic reality in a humorous way. In the theory of linguistic humour by Danuta Buttler, a well-known Polish researcher, typical means to create a humorous effect are: juxtaposition of certain elements, neologisms, rhymes as well as modification of words and expressions. The aim of the present study is to analyse Polish internet memes related to the coronavirus in order to find out what means are used to render the memes studied humorous.